Managing cover crops and nitrogen fertilization to enhance sustainability of sorghum cropping systems in eastern Kansas - Preza Fontes, Giovani (Kansas State University, 2017)
Growing cover crops (CCs) in rotation with cash crops has become popular in recent years for their many agroecosystem benefits, such as influencing nutrient cycling and reducing nutrient losses. This study aimed to (i) determine the long-term effects of no-till with CCs and varying nitrogen (N) rates on subsequent sorghum [Sorghum bicolor (L.) Moench] yield and yield components, (ii) assess how CCs affect the N dynamic in the soil-crop relationship during the growing season and N use efficiency (NUE) of sorghum, and (iii) define and evaluate important periods of nitrous oxide (N₂O) losses throughout the cropping system. Field experiments were conducted during the 2014-15 and 2015-16 growing season in a three-year no-till winter wheat (Triticum aestivum L.) – sorghum – soybean [Glycine max (L.) Merr] rotation. Fallow management consisted of a chemical fallow (CF) control plus four CCs and a double-crop soybean (DSB) grown after wheat harvest. Nitrogen fertilizer was subsurface banded at five rates (0, 45, 90, 135, and 180 kg ha⁻¹) after sorghum planting. On average, DSB and late-maturing soybean (LMS) provided one-third and one-half of the N required for optimum economic grain yield (90 kg N ha⁻¹), respectively; resulting in increased grain yield when compared to the other CCs and CF with 0-N application. Crimson clover (Trifolium incarnatum L.) and daikon radish (Raphanus sativus L.) had no or negative effects on sorghum yield and N uptake relative to CF across all N rates. Sorghum-sudangrass (SS) (Sorghum bicolor var. sudanese) significantly reduced N uptake and grain yield, even at higher N rates. Sorghum following CF had the lowest NUE at optimum grain yield when compared to all CC treatments, suggesting that CCs have a tendency to improve NUE. Cover crops reduced N₂O emissions by 65% during the fallow period when compared to CF; however, DSB and SS increased emissions when N was applied during the sorghum phase, indicating that N fertilization might be the overriding factor. Moreover, about 50% of the total N₂O emissions occurred within 3 weeks after N application, regardless of the cover crop treatment, indicating the importance of implementing N management strategies to reduce N₂O emissions early in the growing season. Overall, these results show that CC selection and N fertilizer management can have significant impacts on sorghum productivity and N₂O emissions in no-till cropping systems.
Keywords: Cover crops; Nitrogen use efficiency; Nitrous oxide emission